Pathological and histochemical changes in the lungs of rabbits experimentally infected with P.seudomonas aeruginosa - H., AL. Kutbi, S.; Alwan, M. J. (The Iraqi Journal of Veterinary Medicine, 2001)
The main objective to this study is to demonstrate certain aspects of pathological and histochomical changes in the lungs of rabbits experimentaly infected with P.aeruginosa . Twelve white Newzoland rabbits of 12-16 weeks old were used . they were randomaly divided into two groups. The first group (6 animals ) were given single intraperitoneal, dose of 108 CFU of P. aeruginosa . The second group (6 animals ) maintained as a control and was inoculated with 1 ml of sterial normal saline by the same route of the first group. All the animals were sacrificed on day three post – inoculation. The pathological exmination showed acute suppurative reaction in pulmonary tissue together with lymphocytic aggregation around airways and blood vessels. The histochomical study revealed that the granules of goblet cells and submucesal glands of the lung in normal rabbits were of neutral mucopolysaecharides and little sialomucin, these substances changed to sulfated acid mucopolysaccharide and sialomucin in the infected animals.